CamDroid: A System for Implementing Intelligent Camera Control - Drucker, Steven; Zeltzer, David (Association for Computing Machinery, Inc., 1995)
A method of encapsulating camera tasks into well defined units called "camera modules" is described. Through this encapsulation, camera modules can be programmed and sequenced, and thus can be used as the underlying framework for controlling the virtual camera in widely disparate types of graphical environments. Two examples of the camera framework are shown: an agent which can film a conversation between two virtual actors and a visual programming language for filming a virtual football game.